1999
DOI: 10.1136/bmj.318.7181.436
|View full text |Cite
|
Sign up to set email alerts
|

Cross sectional study of symptom attribution and recognition of depression and anxiety in primary care   Commentary: There must be limits to the medicalisation of human distress

Abstract: Objectives To examine the effect of patients' causal attributions of common somatic symptoms on recognition by general practitioners of cases of depression and anxiety and to test the hypothesis that normalising attributions make recognition less likely. Design Cross sectional survey. Setting One general practice of eight doctors in Bristol. Subjects 305 general practice attenders. Main outcome measure The rate of detection by general practitioners of cases of depression and anxiety as defined by the general h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
240
1
15

Year Published

2004
2004
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 329 publications
(269 citation statements)
references
References 10 publications
11
240
1
15
Order By: Relevance
“…The results indicated that attributions were often referring to the psychological dimension of the events mentioned by the participants (such as relational problems or death of a relative), even when the events also had a clear somatic dimension, such as violence during childhood, accident, or gynaecological/ obstetrical problems. These results corroborate estimates of patients' psychological distress observed in other studies [43,44] with approximately 60% of patients expressing psychological attributions for various symptoms. Other studies on causal attributions also emphasized the importance of psychological attributions although multiple causal attributions may coexist [16,19].…”
Section: Discussionsupporting
confidence: 90%
“…The results indicated that attributions were often referring to the psychological dimension of the events mentioned by the participants (such as relational problems or death of a relative), even when the events also had a clear somatic dimension, such as violence during childhood, accident, or gynaecological/ obstetrical problems. These results corroborate estimates of patients' psychological distress observed in other studies [43,44] with approximately 60% of patients expressing psychological attributions for various symptoms. Other studies on causal attributions also emphasized the importance of psychological attributions although multiple causal attributions may coexist [16,19].…”
Section: Discussionsupporting
confidence: 90%
“…As a result, there is a need to provide more training for primary care physicians to improve their skills in managing these patients (Von Korff et al 1987;Simpson et al 1991;Kessler et al 1999). Although studies conducted in the West have demonstrated the effectiveness of CME courses in improving doctors' consultation skills, few randomized controlled trials have been conducted in Asia.…”
Section: Practice Pointsmentioning
confidence: 99%
“…These studies are important because although 60% of mental health care is provided in primary care settings, primary care practitioners fail to recognize up to two thirds of the emotional disorders manifested by their patients (Von Korff et al 1987;Kessler et al 1999). Many studies (Borus et al 1988;Young et al 2001) showed that practitioners often lack the skills to detect or deal with psychosocial problems in primary care when patients clearly…”
Section: Introductionmentioning
confidence: 99%
“…As a result, undetected CMD patients go regularly to primary care centers, where complementary exams are excessively requested and they are frequently referred to specialists, or receive inadequate treatment by general practitioners. 13,14 Another important aspect that has been demonstrated is that a higher prevalence of CMD is associated with socio-economic and demographic factors, such as income, gender, education and marital status. [15][16][17][18][19][20][21][22] The association between CMD and low income is so frequent that Patel and Kleinmann have suggested they should be considered a disease associated with poverty.…”
Section: Introductionmentioning
confidence: 99%